Prevalences and Risk Factors Associated with Pre-eclampsia, Low Birth Weight and Post-partum Haemorrhage among Pregnant Women Seeking Antenatal Care in Northern Ghana: A Cross-sectional Descriptive Study - Ahenkorah, Benjamin; Donkor, Addai-Mensah; Opare-Asamoah, Kwame (Pharmaceutical Science: New Insights and Developments Vol. 1, 2024)
The risks of developing pre-eclampsia (PE), giving birth to a low birth weight (LBW) neonate, and post-partum haemorrhage (PPH) among pregnant women in low-and middle-income countries have been on the increase. These risks are further exacerbated in pregnant women from low-resourced settings. This study was therefore conducted to determine the prevalences and risk factors associated with pre-eclampsia, low birth weight and post-partum haemorrhage among pregnant women at antenatal booking in a poor-resourced setting in northern Ghana. Two hundred and sixty-eight pregnant women attending their first antenatal visit at the Bolgatanga Regional Hospital, Bolgatanga, Ghana, from March 2018 to March 2019 took part in the study. The socio-demographic and obstetric characteristics of the pregnant women were obtained through a structured questionnaire. Also, participants' G6PD status, sickling status, blood group, Hb-genotype and Hb (haemoglobin) concentration at 1st ANC visit were determined. A multivariate logistic regression analysis was used to evaluate the risk factors of PE, LBW and PPH. The prevalence of PE, LBW and PPH were 25.4% (68/268), 15.7% (42/268) and 6.0% (16/268), respectively. For PE, delayed 1st ANC visit (AOR=16.82, 95% CI (3.61-78.5), p=0.000) and younger maternal age (AOR= 15.19, 95% CI (1.85-124.56), p=0.011) were independently associated with higher odds. Lastly, delayed 1st ANC visit (AOR=3.26, 95% CI (1.05-10.10), p=0.041) and vaginal delivery (AOR=0.36, 95% CI (0.17-0.74), p=0.006) were independently associated with LBW in the multivariate model. The study identified delayed ANC visits as an independent risk factor for PE, LBW and PPH in Northern Ghana. Public health education for pregnant women that highlights the importance of early ANC visits must be enhanced to facilitate early identification and intervention for women with the risk of foeto-maternal complications. Younger women should be educated on the dangers of early marriages with its attendant foeto-maternal complications of pregnancy.